The Genre of "Fourth Ezra" - Collins, John J. (Rivista di storia del cristianesimo, 2020)
The genre of 4 Ezra is complicated by the formal diversity between the dialogues and the visions, but the different literary forms are not merely juxtaposed. They are arranged to reflect the visionary's progress from agonized skeptic to mediator of revelation. The features that give the book its inner coherence are precisely the features that align it with the apocalyptic genre. The dialogues are subordinated to the revelation, first in the angelic discourses and then more effectively in the visions. The apocalypse views the problems of the present sub specie aeternitatis, not by means of philosophical reasoning but by imaginative vision. It is this transcendent vision of human destiny that is constitutive of the genre apocalypse.